IMPLEMENTASI THEORY OF PLANNED BEHAVIOUR DAN PENGARUHNYA TERHADAP NIAT PEMBELIAN SKINCARE RAMAH LINGKUNGAN PADA GENERASI Z DI INDONESIA - Bagir, Ahmad; Pradito, Pandu; Dewi, Listya; Untung, Untung; Simatupang, Parhimpunan (JURNAL LENTERA BISNIS, 2026)
Objectives This study aims to examine the key factors influencing Generation Z’s intention to purchase environmentally friendly skincare products in Indonesia. Specifically, it investigates the effects of green attitude, perceived behavioral control, and subjective norms using the Theory of Planned Behavior (TPB). Methodology The study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 126 Gen Z respondents with prior experience in using green skincare products. Measurement model evaluation included reliability and validity testing, followed by hypothesis testing using bootstrapping. Finding The results show that green attitude significantly influences green purchase intention, whereas perceived behavioral control and subjective norms do not have a significant impact. This suggests that internal values are more influential than social or situational factors in shaping green purchasing behavior. Conclusion The findings highlight the dominance of attitudinal factors over normative and control-related elements in predicting sustainable skincare consumption among Indonesian Gen Z. Strengthening positive environmental attitudes may be more effective than relying on peer pressure or perceived ability to act.